Hope springs - Black, Todd; Casady, Guymon; Taylor, Vanessa; Frankel, David, 1960-; Streep, Meryl; Jones, Tommy Lee, 1946-; Smart, Jean; Carell, Steve, 1962- (Sony Pictures Home Entertainment, 2012)
Kay and Arnold are a middle-aged couple who have been married for 30 years and now are sleeping in separate rooms and barely interact in any meaningful loving way. Finally, Kay has had enough and finds a book by Dr. Feld which inspires her to sign them up for the doctor's intense week-long marriage counseling session. What follows is an insightful experience as Dr. Feld manages to help the couple understand how they have emotionally drifted apart and what they can do to reignite their passion.